The effectiveness of digital cognitive intervention in patients with traumatic brain injury: systematic review and meta-analysis - Chi, Kejia; Chen, Jiangfeng; Zhou, Shiwei; Han, Zheqi (Frontiers in Neurology, 2025)
ObjectiveThis meta-analysis aims to quantitatively evaluate the effects of digital cognitive intervention (non-immersive computer- and immersive virtual reality (VR)-based) on cognitive function and psychosocial outcomes in patients with traumatic brain injury (TBI), and to explore potential moderating factors.MethodsA systematic search was conducted in PubMed, the Cochrane Library, Embase, and Web of Science databases from their inception to April 3, 2025. Standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculated to estimate effect sizes, and heterogeneity was assessed using the I2 statistic.ResultsA total of 16 studies were included; 9 employed computer-based cognitive interventions and 7 used VR-based interventions. The results showed that both types of interventions significantly improved global cognitive function (SMD: 0.64, 95% CI: 0.44 to 0.85, I2 = 0%), executive function (SMD: 0.32, 95% CI: 0.17 to 0.47, I2 = 15%), attention (SMD: 0.40, 95% CI: 0.02 to 0.78, I2 = 0%) and social cognitive function (SMD: 0.46, 95% CI: 0.20 to 0.72, I2 = 0%) in TBI patients. However, no significant improvements were observed in memory, processing speed, activities of daily living, or psychosocial outcomes (self-efficacy, anxiety/depression). Subgroup analysis indicated that VR-based interventions were more effective than traditional cognitive therapy. Moreover, VR interventions had a positive effect on depression in TBI patients. A greater number of training sessions may further enhance cognitive benefits.ConclusionThis meta-analysis supports the efficacy of digital cognitive intervention in improving cognitive function in TBI patients. We recommend individualized treatment programs to more effectively address cognitive impairments.